Thermal expansion of Ti-Al-N and Cr-Al-N coatings. (15th January 2017) - Bartosik, M.; Holec, D.; Apel, D.; Klaus, M.; Genzel, C.; Keckes, J.; Arndt, M.; Polcik, P.; Koller, C.M.; Mayrhofer, P.H.
Abstract: The thermal expansion coefficients (TECs) of B1 structured Ti1 − x Alx N and Cr1 − x Alx N thin films – investigated by synchrotron X-ray diffraction from room temperature to 600 °C – excellently agree with ab initio obtained temperature dependent calculations only if they were annealed at 600 °C. As-deposited thin films, with their built-in structural defects show a lower temperature dependence of their TECs and higher values. Furthermore, our data clearly show that the TECs of cubic Ti1 − x Alx N and Cr1 − x Alx N increase with increasing Al content, and that the TEC of wurtzite type B4 structured AlN is only about half of that of B1 AlN. Graphical abstract: